A modificação subjetiva do contrato administrativo e sua execução total ou parcial por terceiros - Penna, Rodolfo Breciani (2024)
The objective of this work is to analyze the forms and validity of third-party participation in administrative contract from the perspective of the Federal Constitution, law, jurisprudence and doctrine, especially confronting the model adopted by the legislator with the assertions of incompatibility with the bidding, with impersonality and with the traditional academic statement about the very personal nature of administrative contracts. In this task, through qualitative and applied bibliographical research, we analyze, in the first part of the work, the concept of administrative contract, support its contractual nature and establish initial premises that will guide the study. Then, we scrutinize the Federal Constitution and the law about these public contracts. On the other hand, we present the discussion about the very personal nature of administrative contracts, rejecting this statement, as well as the allegation of the need for bidding for the execution of these contracts by third parties, also rejecting these arguments. We proceed, in sequence, to an analysis of foreign legislation on the subject and the practical consequences generated by the related legal institutes. Therefore, in the second part of the work, we analyze in detail the legal institutes related to the subjective modification of administrative contracts and their total or partial execution by third parties, reflecting on the main problems, questions and presenting solutions. Finally, we analyze the main controversies about the previously studied institutes and try to systematize a minimum legal regime for the participation of third parties in administrative contracts. We conclude, therefore, that, as a rule, administrative contracts are not very personal, only being so when the nature of the specific contract so requires, so that there is not invalidity or unconstitutionality in the forms of participation of third parties in administrative contracts. In addition, we present the most relevant contours related to the institutes that allow the subjective modification of contracts and their execution by third parties